2023
DOI: 10.3390/su152014814
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Dimension of Corporate Social Responsibility and Earnings Persistence: An Exploration of the Moderator Roles of Operating Efficiency and Financing Cost

Yongming Zhang,
Mohsen Imeni,
Seyyed Ahmad Edalatpanah

Abstract: Society has gradually realized that companies’ actions have consequences. Companies can fulfill their accountability to society by disclosing information beyond their financial data, providing better decision making for stakeholders. Therefore, this study aims to investigate the impact of corporate social responsibility (CSR) on earnings persistence (EP) for the moderator roles of operational efficiency and financing cost for the companies listed on the Tehran Stock Exchange. For this purpose, the statistical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 104 publications
1
2
0
Order By: Relevance
“…The mean of discretionary accruals approximates zero for heavy-polluting firms, consistent with previous studies results [27,29]. The results of the descriptive statistics for the remaining control variables are also similar to the existing literature [50,51].…”
Section: Descriptive Statistics and Correlationssupporting
confidence: 90%
“…The mean of discretionary accruals approximates zero for heavy-polluting firms, consistent with previous studies results [27,29]. The results of the descriptive statistics for the remaining control variables are also similar to the existing literature [50,51].…”
Section: Descriptive Statistics and Correlationssupporting
confidence: 90%
“…The authors observed that changing traditional auditing processes and applying new technologies require work methods and organizational culture changes. They also emphasized ethical issues and responsibility in using AI in the auditing and accounting processes (Zhang et al 2023).…”
Section: Ai In the Accounting Fieldmentioning
confidence: 99%
“…In the TAM, the intention to use technology is the likelihood that an individual will apply a particular technology, leading to the behavior of applying or using a specific technology (Zhang et al 2023). The TAM posits that the acceptance of a new system is determined by users having the intention to use the system, which is influenced by users' trust in the system's ease of use (PEOU) and usefulness (PU) (Salman and Ismael 2023).…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%